Effects of Ramadan and Non-ramadan Intermittent Fasting on Body Composition: A Systematic Review and Meta-Analysis - Correia, Joana M.; Santos, Inês; Pezarat-Correia, Pedro; Silva, Analiza M.; Mendonca, Goncalo V. (Frontiers in Nutrition, 2021)
Intermittent fasting (IF) has gained popularity for body-composition improvement purposes. The aim of this systematic review and meta-analysis was to summarize the effects of Ramadan vs. non-Ramadan IF on parameters of body composition. We conducted a comprehensive search of peer-reviewed articles in three electronic databases: PubMed, Scopus and Web of Science (published until May 2020). Studies were selected if they included samples of adults (≥18 years), had an experimental or observational design, investigated any type of IF and included body composition outcomes. Meta-analytical procedures were conducted when feasible. Sixty-six articles met the eligibility criteria. We found that non-Ramadan IF is effective for decreasing body weight (-0.341 (95% CI [-0.584, -0.098], p = 0.006), body mass index (-0.699, 95% CI [-1.05, -0.347], p < 0.001), and absolute fat mass (-0.447, 95% CI [-0.673, -0.221], p < 0.001). When contrasting pre- post-intervention data on fat-free mass between treatments and controls, group-differences were non-significant (p > 0.05). Conversely, we observed a significant increase in fat-free mass when comparing pre- to post-intervention in a within design fashion (0.306, 95% CI [0.133, 0.48], p = 0.001). Finally, despite being accompanied by dehydration, Ramadan IF seemed to be effective in decreasing body weight (-0.353; 95% CI [-0.651, -0.054], p = 0.02) and relative fat mass (-0.533; 95% CI [−1.025, -0.04], p = 0.034). Ramadan IF seems to implicate some beneficial adaptations in weight management, although non-Ramadan IF appears to be more effective in improving overall body composition.